(untitled) (Altre Modernità, 2014)
After a brief discussion of Grete Weil’s liminal position in the context of Twentieth-Century German-Jewish Women’s Literature, the present contribution outlines the key issues of her prose works between 1949 and 1999 and focuses then on her third novel, Generations (1983). As a matter of fact, this often neglected work proves to be a metafiction exploring the possibilities, frustrations and success of German-Jewish Women’s writing in post-war West Germany. Thus, a new interpretation of this audacious novel is put forward. Whereas both the deconstruction of cultural taboos and the construction of a dialogue between three generations of women fail in the fictional “experiment”, they are actually achieved in the literary act of writing.